2023
DOI: 10.1111/1460-6984.12866
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of speech–language pathologists’ approaches in treating spoken discourse post‐traumatic brain injury

Abstract: BackgroundSpoken discourse impairments post‐traumatic brain injury (TBI) are well‐documented and heterogeneous in nature. These impairments have chronic implications for adults in terms of employment, socializing and community involvement. Intervention delivered by a speech–language pathologist (SLP) is recommended for adults with discourse impairments post‐TBI, with an emphasis on context‐sensitive treatment. The developing evidence base indicates a wide array of treatment components for SLPs to evaluate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Steel et al (2022) observed some markers of success in translation of evidence-based approaches to management of discourse after TBI, with most of the surveyed clinicians in their study reporting the use of discourse-level tasks in communication assessment, and an individualised goal-based approach to intervention. Hoffman et al (2023) similarly found the interviewed clinicians in their study employed evidence-based principles when targeting discourse after TBI, such as contextsensitive treatment, using group service delivery and communication partner training, and tailoring to individual client needs. The findings of these two studies (Hoffman et al, 2023;Steel et al, 2022) (Togher et al, 2023).…”
Section: Investigating Translation From Research To Practicementioning
confidence: 86%
See 1 more Smart Citation
“…Steel et al (2022) observed some markers of success in translation of evidence-based approaches to management of discourse after TBI, with most of the surveyed clinicians in their study reporting the use of discourse-level tasks in communication assessment, and an individualised goal-based approach to intervention. Hoffman et al (2023) similarly found the interviewed clinicians in their study employed evidence-based principles when targeting discourse after TBI, such as contextsensitive treatment, using group service delivery and communication partner training, and tailoring to individual client needs. The findings of these two studies (Hoffman et al, 2023;Steel et al, 2022) (Togher et al, 2023).…”
Section: Investigating Translation From Research To Practicementioning
confidence: 86%
“…Hoffman et al (2023) similarly found the interviewed clinicians in their study employed evidence-based principles when targeting discourse after TBI, such as contextsensitive treatment, using group service delivery and communication partner training, and tailoring to individual client needs. The findings of these two studies (Hoffman et al, 2023;Steel et al, 2022) (Togher et al, 2023). There is also an audit tool to assist clinicians and managers to monitor guidance adherence via clinical file audits.…”
Section: Investigating Translation From Research To Practicementioning
confidence: 86%